Fuzzy Generalized Conformable Fractional Derivative. (6th February 2020) - Harir, Atimad; Melliani, Said; Chadli, Lalla Saadia
Abstract : We give a new definition of fuzzy fractional derivative called fuzzy conformable fractional derivative. Using this definition, we prove some results and we introduce new definition of generalized fuzzy conformable fractional derivative.